catena-Poly[[diaquabis(1H-imidazole-κN (3))cobalt(II)]-μ-2,3,5,6-tetrachloroterephthalato-κ(2) O (1):O (4)] - Zheng, Chang-Ge (International Union of Crystallography, 2012)
In the title compound, [Co(C(8)Cl(4)O(4))(C(3)H(4)N(2))(2)(H(2)O)(2)](n), the Co(II) ion displays a distorted octahedral coordination geometry with two O atoms from two monodentate tetrachloroterephthalate dianions, two N atoms from two imidazole molecules and two O atoms from two water molecules. The Co(II) ions are connected via the tetrachloroterephthalate dianions into a chain running along the crystallographic [110] direction. Adjacent chains are linked into a two-dimensional network arranged parallel to (010) by classical N—H⋯O and O—H⋯O hydrogen bonds.